2018
DOI: 10.7554/elife.34488
|View full text |Cite
|
Sign up to set email alerts
|

Independent evolution of functionally exchangeable mitochondrial outer membrane import complexes

Abstract: Assembly and/or insertion of a subset of mitochondrial outer membrane (MOM) proteins, including subunits of the main MOM translocase, require the fungi-specific Mim1/Mim2 complex. So far it was unclear which proteins accomplish this task in other eukaryotes. Here, we show by reciprocal complementation that the MOM protein pATOM36 of trypanosomes is a functional analogue of yeast Mim1/Mim2 complex, even though these proteins show neither sequence nor topological similarity. Expression of pATOM36 rescues almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 40 publications
(84 reference statements)
0
33
0
Order By: Relevance
“…However, if so, Atg43 may not necessarily be involved in all of the import events mediated by the MIM complex, as the mitochondrial loading of Tom70 is highly dependent on the MIM complex but not on Atg43. Alternatively, similar to pATOM36 of trypanosomes, a functional analog of the MIM complex, Atg43 and the MIM complex may contribute to mitochondrial DNA segregation ( Vitali et al, 2018 ). Notably, the C-terminal component of Atg43, which is required for the interaction with the MIM complex and normal cell growth, is shared among fungi.…”
Section: Discussionmentioning
confidence: 99%
“…However, if so, Atg43 may not necessarily be involved in all of the import events mediated by the MIM complex, as the mitochondrial loading of Tom70 is highly dependent on the MIM complex but not on Atg43. Alternatively, similar to pATOM36 of trypanosomes, a functional analog of the MIM complex, Atg43 and the MIM complex may contribute to mitochondrial DNA segregation ( Vitali et al, 2018 ). Notably, the C-terminal component of Atg43, which is required for the interaction with the MIM complex and normal cell growth, is shared among fungi.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that the Trypanosoma brucei protein pATOM36 can functionally compensate the absence of the MIM complex (Vitali et al, 2018). Hence, we next aimed to test whether this protein can also replace the MIM function in facilitating the membrane integration of the two new substrates that we identified, Atg32 and Gem1.…”
Section: The Mim Complex Contributes To the Membrane Integration Of Tmentioning
confidence: 99%
“…Remarkably, pATOM36 is not only essential for TAC function, but also for the biogenesis of a subset of mitochondrial OM proteins (Käser et al, 2016). In fact, experiments in yeast and T. brucei have revealed that pATOM36 is a functional analog of the yeast mitochondrial inner-membrane import machinery (MIM) complex, which consists of Mim1 and Mim2 (Vitali et al, 2018). In line with its dual function, pATOM36 localizes to the DM subdomain of the TAC, as well as all over the OM (Käser et al, 2016).…”
Section: Tac Subunits -Dmmentioning
confidence: 99%